The secret explorers and the Jurassic rescue - King, SJ (King, SJ. Secret Explorers, 2020)
In The Secret Explorers and the Archaeopteryx Egg, dinosaur expert Tamiko and geology expert Cheng travel back to the age of the dinosaurs in an effort to rescue a dinosaur egg from destruction. However, to save the egg, the Secret Explorers first have to use all their courage and skills to outsmart a fierce Allosaurus, rescue a baby Stegosaurus, and find a way to attract an Archaeopteryx. Tamiko and Cheng soon find that, to succeed, they need to come up with some unusual solutions...Packed with fun illustrations and facts about dinosaurs, fossils, and why modern birds are dinosaurs, this thrilling adventure is perfect for young readers. Informative diagrams tell kids all they need to know about different species of dinosaur, from Stegosaurus to Allosaurus. The action-packed narrative keeps kids engaged and makes learning about dinosaurs even more fun!